Types and abundance of zooplankton in the SamsamSwamp, Kandis Sub-District, Siak District, Riau Province - Muzdalifah '; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Samsam swamp is located in the peat swamp area and flooded during rainy season. A research aims to understand the type and abundance of zooplankton in the Samsam swamp, has been carried out in March 2016. There were 4 stations, namely S1 is in the upstream (almost no human activity); S2 (around palm plantation); S3 (around the newly planted palm plantation) and S4 (far from palm plantation). Sampling were conducted 3 times, once/week. Results shown that zooplankton in the Samsam Swamp was consisted of 5 Classes (14 species). The most common species was crustacean (4 species). The average of zooplankton abundance was around 194-833 organisms/L, species diversity index (H’) was 2,573-3,596, equatibility index (E) was 0.66-0.92, and dominance index (C) was 0.089-0.274. While the water quality parameters were as follows: temperature: 30-320C, transparency: 30-40 cm, depth: 83-114 cm, pH: 4-5, CO2: 8.66-9.32 mg/L, DO:3.96-4.65 mg/L, nitrate:0.45-0.58 mg/L and phosphate:0.36-0.56 mg/L. Based on data obtained it can be concluded that zooplankton diversity was medium, nodominant speciesand the water quality is able to support the life of aquatic organisms.Keyword :Zooplankton, Kandis Sub-District, Samsam Swamp